A Cylindrical Cell for Operando Neutron Diffraction of Li-Ion Battery Electrode Materials - Vitoux, Laura; Reichardt, Martin; Sallard, Sébastien; Novák, Petr; Sheptyakov, Denis; Villevieille, Claire (Frontiers in Energy Research, 2018)
Neutron diffraction is a powerful technique to localize and quantity lithium in battery electrode materials. However, obtaining high-quality Operando neutron diffraction data is challenging because it requires achieving good electrochemical performance while cycling a large amount of active material to ensure optimal signal-to-noise ratios. We have developed a cylindrical cell specifically suited for operando neutron studies, and used it to investigate the structural changes in the Ni-rich LiNi0.6Co0.2Mn0.2O2 cathode material during cycling between 2.5 and 4.3 V vs Li+/Li. The cell demonstrates reliable electrochemical performance, even after long-term cycling, and the important crystal structure parameters of the active material, including Li occupancy, could be successfully refined with the Rietveld method using neutron diffraction data collected in operando after appropriate background subtraction.